Study of vegetable okra by microwave remote sensing at X- band - Pandey A.; Prasad R.; Rajput N.S. (My University, 2025)
Okra commonly known as lady finger is one of the important vegetable cultivated in India. Today Remote sensing is an important tool for monitoring the crop production. For this purpose we use bistatic microwave scatterometer working at X-band (9.5 GHz). Biomass factor and leaf area index is calculated within this period. Scattering coefficient (σ) and their dependence on look angle were analyzed. In this way by using the Biomass, Leaf area index and scattering coefficient an idea is developed which is helpful for radar sensors and also helpful for the production monitoring of this vegetable.